Pharmacogenetics in the Brazilian Population - Suarez-Kurtz, Guilherme (Frontiers in Pharmacology, 2010)
Brazil is the 5th largest country in the world and its present population, in excess of 190 million, is highly heterogeneous, as a result of centuries of admixture between Amerindians, Europeans and Sub-Saharan Africans. The estimated individual proportions of biogeographical ancestry vary widely and continuously among Brazilians, most individuals - irrespective of self-identification as White, Brown or Black, the major categories of the Brazilian Census “race/color” system - having significant degrees of European and African ancestry, while a sizeable number display also Amerindian ancestry. These features have important pharmacogenetic (PGx) implications: first, extrapolation of PGx data from relatively well-defined ethnic groups is clearly not applicable to the majority of Brazilians; second, the frequency distribution of polymorphisms in pharmacogenes (e.g. CYP3A5, CYP2C9, GSTM1, ABCB1, GSTM3, VKORC, etc) varies continuously among Brazilians and is not captured by race/color self-identification; third, the intrinsic heterogeneity of the Brazilian population must be acknowledged in the design and interpretation of PGx studies in order to avoid spurious conclusions based on improper matching of study cohorts. The peculiarities of PGx in Brazilians are illustrated with data for different therapeutic groups, such as anticoagulants, HIV-protease inhibitors and nonsteroidal antinflammatory drugs, and the challenges and advantages created by population admixture for the study and implementation of PGx are discussed. PGx data for Amerindian groups and Brazilian-born, first generation Japanese are presented to illustrate the rich diversity of the Brazilian population. Finally, I introduce the reader to the Brazilian Pharmacogenetic Network or Refargen (www.refargen.org.br), a nationwide consortium of research groups, with the mission to provide leadership in PGx research and education in Brazil, with a population health impact.